Review—Hexagonal Boron Nitride Epilayers: Growth, Optical Properties and Device Applications. (1st January 2017) - Jiang, H. X.; Lin, J. Y.
Abstract : This paper provides a brief overview on recent advances made in authors' laboratory in epitaxial growth and optical studies of hexagonal boron nitride ( h- BN) epilayers and heterostructures. Photoluminescence spectroscopy has been employed to probe the optical properties of h- BN. It was observed that the near band edge emission of h- BN is unusually high and is more than two orders of magnitude higher than that of high quality AlN epilayers. It was shown that the unique quasi-2D nature induced by the layered structure of h- BN results in high optical absorption and emission. The impurity related and near band-edge transitions in h- BN epilayers were probed for materials synthesized under varying ammonia flow rates. Our results have identified that the most dominant impurities and deep level defects in h- BN epilayers are related to nitrogen vacancies. By growing h- BN under high ammonia flow rates, nitrogen vacancy related defects can be eliminated and epilayers exhibiting pure free exciton emission have been obtained. Deep UV and thermal neutron detectors based on h -BN epilayers were shown to possess unique features. It is our belief that h- BN will lead to many potential applications from deep UV emitters and detectors, radiation detectors, to novel 2D photonic and electronic devices.